Cryptic translocation involving two acrocentric chromosome ends revealed by fluorescence in situ hybridization after two consecutive pregnancies of which the results of chromosome microarray were mirror-imaged - Yao-Lung Chang; Hsiu-Huei Peng; Hsueh-Chun Cheng; Chi-Yuan Chiang; Ho-Yen Chueh; Yu-Ting Lin; Chin-Pei Lee; Shuenn-Dyh Chang; Ming Chen (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Prenatal diagnosis of fetal 13q34 microdeletion is a rare condition, which may present with abnormal fetal development, including facial dysmorphism, mental retardation, and developmental delay. We present a pregnant woman in whom the fetus presented with a 0.24-cm ventricular septal defect at 20 weeks of gestation, with fetal 13q34 (113610612–115092648) deletion. Previous fetus of the woman had 13q34 (113610612–115092648) duplication and normal prenatal ultrasound findings. Further parental karyotype, parental microarray-based comparative genomic hybridization (array CGH), and fluorescence in situ hybridization (FISH) study were performed to clarify this issue. Case Report: In a 44-year-old pregnant woman, amniocentesis revealed a fetal karyotype of 46, XY,13qs and microarray-based comparative genomic hybridization (array CGH) showed 13q34 (113610612–115092948) deletion. Prenatal ultrasound at 20 weeks of gestation revealed normal fetal structure except ventricular septal defect 0.24 cm. The parents had strong desire to continue pregnancy even the possibility of mental or developmental issues.Tracing back to her previous pregnancy, amniocentesis for the previous fetal karyotype revealed a normal 46, XX, and array CGH showed 13q34 (113610612–115092948) duplication. Prenatal ultrasound at 21 weeks of gestation revealed normal fetal structure. The parents decided to continue pregnancy and the baby was born at term with normal postnatal development. Parental karyotyping revealed maternal 46, XX and paternal 46, XY,13qs, and both array CGH were normal. Further paternal FISH study found 46,XY, t(13;22) (q34;p12).ish t(13;22) (Acro-p++; Acro-p+, LMP1+, D13S1825+), revealing translocation of the subtelomeric 13q and chromosomal 22 p arm. Based on these findings, the fetal karyotype in previous pregnancy should be 46,XX,der(22), t(13;22) (q34;p12).arr[GRCh37] 13q34 (113610612–115092648) × 3 pat. The fetal karyotype in this pregnancy should be 46,XY,der(13), t(13;22) (q34;p12).arr[GRCh37] 13q34 (113610612–115092648) × 1 pat. Conclusion: Fetal 13q34 microdeletion may present with fetal ventricular septal defect on prenatal ultrasound. Fetal 13q34 microduplication with subsequent fetal 13q34 microdeletion is rare. Our case underscores the importance of the parental karyotype, parental array CGH, combined with FISH study to clarify this issue.